The modulating effects of brain stimulation on emotion regulation and decision-making. Issue 1 (December 2016) - Choi, Kyung; Scott, David; Lim, Seung-Lark
Abstract Background It has been reported that brain stimulation such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) can modulate a variety of cognitions and emotions in humans. rTMS and tDCS studies provide strong possibilities of applications in the manipulation of emotion regulation and decision-making in humans. Methods We searched the literature by using keywords "rTMS, " "tDCS, " "emotion regulation, " and "decision-making" on PubMed (http://www.ncbi.nlm.nih.gov/pubmed ). Based on the search results, we reviewed studies on emotion regulation and decision-making using rTMS and tDCS modulations. Results Regarding emotion regulation, rTMS can influence both attentional and affective aspects of emotion regulation. tDCS studies for emotion regulation included diverse topics such as physiological arousal, social exclusion, mathematics anxiety, emotional reactions to pain stimuli, negative affect, momentary ruminative self-referent thoughts, and autonomic reactions to affective pictures. Decision-making studies have reported rTMS effects related to emotion such as delay-discounting tasks, food choice, and moral judgment. These studies have also investigated cognitive functions such as visuospatial attention, perception, object identification, spatial-working memory, visuomotor skills, task, and blameworthiness and punishment decisions. In tDCS studies for decision-making, it has increasingly been reported that tDCS influences moral judgment, risk-taking behaviors, choice modulation, delay discounting, maladaptive and perceptual decision-making, probabilistic guessing, perception of space and time, dual-task performance, model-based learning, addiction, food craving, sunk-cost effect, exploration-exploitation trade-offs and cognitive impulse control. Conclusion rTMS and tDCS have been shown to modulate behaviors relevant to emotion regulation and decision-making. The results of these numerous studies can be applied to clinical populations, and demonstrate that rTMS and tDCS may have many beneficial implications to those who have emotion regulation deficiencies.